Land Cover Changes of Pangandaran: Revealing the Tourism Attraction Impact on Coastal Urban Expansion - Abdurrahman, Umar; Iskandar, Zahara Sitta; Subiyanto, Subiyanto; Maqbul, Ismail; Alina, Dining Nika; Ismail, Mochamad Rudyansyah (International Journal of Research in Community Services, 2025)
Land cover changes in the Pangandaran Coastal area are significantly influenced by tourism attractions as well as geographic and socio-economic dynamics. As one of the main coastal tourism destinations in West Java, Pangandaran receives more than 3.5 million tourists annually, which puts significant pressure on the coastal environment. This study uses land cover data from 2017–2023 analyzed using a regression and GIS approach, this study identifies spatial and temporal patterns of urban expansion and their implications for environmental sustainability. The results show that urbanization in Pangandaran is concentrated in the coastal lowlands, especially in Pangandaran and Sidamulih Districts, increasing vulnerability to natural disasters such as tsunamis. This expansion is triggered by the need for tourism infrastructure that often sacrifices natural ecosystems such as mangroves and coastal forests. In Cimerak and Parigi Districts, changes are more influenced by industrial and agro-industrial development, while growth in Cijulang is hampered by karst topography which is less supportive of urban development. Meanwhile, Kalipucang remains relatively natural due to geographic limitations that limit urban expansion. This study emphasizes the importance of sustainable coastal management, including adaptive spatial planning, conservation of critical ecosystems, and community-based initiatives to mitigate risks posed by unplanned urban expansion. The results of this study provide important insights for policymakers to balance tourism-based development with environmental resilience in the coastal area of Pangandaran.